THE CLOUD TECHNOLOGIES IN PROFESSIONAL EDUCATION OF THE FUTURE ECONOMISTS - Dyulicheva Ю.Ю. (Journal of Information Technologies in Education (ITE), 2015)
The usage of the cloud services in the professional education of the future economists are investigated. The following cloud services are analyzed in the paper: 1) the cloud service gantter for project management, its resources management, risks evaluation with example of the capabilities for Ganter diagram creation, project critical path determination based on gantter cloud service are considered; 2) the cloud service SageMath Cloud with capabilities of programming languages R, Python, Cython GAP usage for data analysis with example of the linear regression model construction on data sample based on the language R usage are considered; 3) Google’s cloud service based on the spreadsheets for the linear programming problems solving based on the tool Solver for the linear optimization problem is investigated; 4) the educational project Big Data University the main goal of which is learning of the students to handle big data based on the cloud technologies with the capabilities to learn request language SQL, language R for data analyses and the methods for data warehouse preprocessing are considered; 5) the cloud services from «1С» and «BuhSoft» studying of the accounting information systems with the reports creation and payroll capabilities are analyzed.